Reimagining the research-practice relationship: policy recommendations for informatics-enabled evidence-generation across the US health system. Issue 1 (16th January 2019) - Embi, Peter J; Richesson, Rachel; Tenenbaum, Jessica; Kannry, Joseph; Friedman, Charles; Sarkar, Indra Neil; Smith, Jeff; ,
Abstract: The widespread adoption and use of electronic health records and their use to enable learning health systems (LHS) holds great promise to accelerate both evidence-generating medicine (EGM) and evidence-based medicine (EBM), thereby enabling a LHS. In 2016, AMIA convened its 10th annual Policy Invitational to discuss issues key to facilitating the EGM-EBM paradigm at points-of-care ( nodes ), across organizations ( networks ), and to ensure viability of this model at scale ( sustainability ). In this article, we synthesize discussions from the conference and supplements those deliberations with relevant context to inform ongoing policy development. Specifically, we explore and suggest public policies needed to facilitate EGM-EBM activities on a national scale, particularly those policies that can enable and improve clinical and health services research at the point-of-care, accelerate biomedical discovery, and facilitate translation of findings to improve the health of individuals and populations.